The Relationship between Teachers’ Belief Systems, Creativity and the Use of Technology-Based English Teaching - Abbasi, Wajahat Taj; Ainol Haryati, Ibrahim; Fatimah, Ali (Universiti Malaysia Pahang, 2022)
This study intends to find out teachers’ belief systems, its’ relevant factors and teachers’ creativity which may influence the use of technology for teaching of English at undergraduate level in Islamabad, Pakistan. The study highlights certain problems faced by teachers under belief system and the relevant factors in their implementation of Information and Communication Technology (ICT) for teaching of English inside classrooms. Data was collected through a questionnaire questionnaire based on Decomposed Theory of Planned Behavior (DTPB) from 31 ESL teachers teaching at different colleges in the capital of Pakistan [Islamabad] to know their perceptions, opinions and ideas regarding barriers confronted by them in the implementation of technology for teaching English as Second Language (ESL). Data is analyzed with the help of SPSS 22. The findings of the study revealed internal and external barriers such as beliefs, attitudes, behaviors, subjective norms, professional development, resources, and cross culturalism faced by teachers for incorporating innovation and creativity in their teaching practices through the use of technology in Pakistan. The study concludes with recommendations and suggestions for further research.